Ekonomie in die tyd van die Bybel as "n huishouding-gebaseerde ekonomie - Volschenk, G. J. (HTS teologiese studies, 2003)
Economy in the time of the Bible as a household based economyThe aim of this article is to describe the economy in the time of the Bible as a household economy. Firstly, the results of social scientific research indicated that the family institution was the primary socio-economic and political building block of the first century Mediterranean world. Secondly, the social scientific model of the pre-industrial city is used as interpretation framework for the first century Mediterranean economy. The article concludes with a reflection on the exploitation of peasants by urban elite and aristocrats. They were absent landowners who controlled the land and production on the land.